First record of Monarthropalpus buxi in Greece and some data of its phenology - Vamvakas, M.; Kontodimas, D.C.; Milonas, P.G. (ENTOMOLOGIA HELLENICA, 2006)
The gall inducing insect Monarthropalpus buxi (Laboulbene) (Diptera: Cecidomyiidae) has been recorded in Greece on 20/4/2004 in Athens (Ellinikon, GPS point: N 370 54’ 22”, E 23° 44’ 34”) on Buxus roduntifolia. Two-20 larvae per infested leaf were noticed but only 2-3 adults per leaf emerged. The majority (>92%) of the population of M. buxi completed one generation per year and adults emerged from late April to early May. A small proportion (<8%) of the population completed two generations per year and I generation adults emerged from late January to late March. Second generation adults emerged from late June to late July. In addition, during 2006 parasitism by Torymus sp. (Hymenoptera: Torymidae) on larvae of the fly has been noticed.